2012
DOI: 10.1186/1478-4505-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Building tobacco control research in Thailand: meeting the need for innovative change in Asia

Abstract: IntroductionIn low- and middle-income countries (LMICs) over the past two decades locally relevant tobacco control research has been scant. Experience shows that tobacco control measures should be based on sound research findings to ensure that measures are appropriate for local conditions and that they are likely to have an impact. Research should also be integrated within tobacco control measures to ensure ongoing learning and the production of knowledge. Thailand, a middle-income country, has a public healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“… I think they (government) are not taking it (tobacco control) as a big issue. Tobacco, being a low priority issue, is a concern not only in India but also in many other developing and even developed countries [ 5 , 23 25 ]. A study conducted in Australia regarding the translation of the tobacco control policy into practice found that tobacco was considered as a low priority issue and therefore the impact of policy was insignificant [ 26 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… I think they (government) are not taking it (tobacco control) as a big issue. Tobacco, being a low priority issue, is a concern not only in India but also in many other developing and even developed countries [ 5 , 23 25 ]. A study conducted in Australia regarding the translation of the tobacco control policy into practice found that tobacco was considered as a low priority issue and therefore the impact of policy was insignificant [ 26 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Studies from developing [ 30 ] and developed countries [ 25 , 27 ] suggest similar barriers such as shortage of human resource and the shortage of information, education, and communication materials hampering effective implementation of tobacco control policy and program. We (program managers) need funds, manpower, material.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…While the WHO was held in high regard for their technical advice, 45,55,60,63,98 sources also highlighted multisectoral consensus building to derive from engagement with the Food and Agriculture Organization (FAO), IMF, the World Bank, and other national and international NGOs and philanthropic trusts. 53,61,62,68,71,73,104,113 Locally-based offices of multilateral agencies, seed organisations and links between multi-lateral actors and local organisations sometimes blurred the boundaries between multilateral and civil society action. Financing and the supplementation of national economic, technical and legal capacities were the predominant forms of support, with each noted to be beneficial in overcoming common LMIC capacity constraints.…”
Section: Multilateral Actorsmentioning
confidence: 99%
“…Studies which assessed factors that impede tobacco control research in low and middle income countries have shown consistently that funding, infrastructure, resources are the most challenging impediments to building up tobacco control research [ 17 – 19 ]. Similarly, in our study experts from all professional affiliations chose funding issues as most important factor impeding formation of tobacco research network in both the rounds of survey.…”
Section: Discussionmentioning
confidence: 99%